Rasch politomy analysis: measuring the level of student senior high school resilience after the disaster in West Sumatra - Erwinda, Lira; Syahputra, Yuda; Fadli, Rima Pratiwi; Zola, Nilma (Konselor, 2018)
The purpose of the study was to measure the level of resilience of high school students in West Sumatra. This study involved 378 students in atasse-West Sumatra secondary school, the data in this study were in the form of political data collected using the TIRI (Taufik & Ifdil Resilience Inventory) instrument developed from the theory of Reivich & ShattÃ©, (2002) in the form of Likertâ€™s model scale and analyzed data using the Rasch model approach. The results show that most students are at a high level of resilience. In addition, there are 38 students unsuitable in providing answers or outliers, showed there are traces of fraud, or answers the instrument by guessing. The quality of the TIRI instrument given to students is superb for identifying post-disaster resilience conditions, as seen from the reliability value of the item (.99).